Foliar diseases and mycoflora associated with diseased leaf of cinnamon (Cinnamomum verum J. Presl) from Bangladesh - Naher, N; Shamsi, S (Journal of Biodiversity Conservation and Bioresource Management, 2025)
Cinnamon (Cinnamomum verum J. Presl) is an important spice with medicinal value worldwide. Three foliar diseases, such as small leaf spots, gray leaf blight and leaf blight were recorded from September 2022 to August 2023 at three different locations in Bangladesh. Disease incidence of gray leaf spots recorded from the location of Savar was highest in about 48% and small leaf spots from Dhaka (68%) and leaf blight disease from the location of Savar (88%). A total of six species of fungi such as Aspergillus flavus, A. fumigatus, A. niger, Fusarium sp., Rhizomucor miehei and Colletotrichum gloeosporioides were recorded from small leaf spots symptom. Highest frequency of occurrence of the fungus was R. miehei (66.67%) followed by C. gloeosporioides was 62.50%. Four fungal species such as A. flavus, A. fumigatus, A. niger and Pestalotiopsis palmarum were isolated from gray leaf spots symptom of the leaves of Cinnamomum verum. Highest frequency recorded from P. palmarum was 83.33 %. Five fungal species were isolated from leaf blight disease symptoms of C. verum were A. fumigatus, A. niger, C. gloeosporioides, Fusarium sp. and R. miehei. Frequency percentage of C. gloeosporioides was highest 75.00% and Fusarium sp. was lowest 8.33%. Among the fungi isolated from three disease symptoms, three fungi such as C. gloeosporioides, P. palmarum and R. miehei were capable to produce symptoms of leaves. Seven species of fungi viz. A. flvaus, A. niger, C. gloeosporioides, Colletotrichum sp., Fusarium sp., P. palmarum, Rhizopus sp. and one sterile fungus were recorded from associated with the different disease symptoms of cinnamon leaf in moist chamber methods. J. biodivers. conserv. bioresour. manag. 10(2), 2024: 59-68